The Buddha was a devoted nationalist Buddhist nationalism, ressentiment, and defending Buddhism in Myanmar - Foxeus, Niklas 1967- (2019)
Since 2012, Buddhist nationalist movements - especially the 969 movement and Ma Ba Tha - have emerged in Burma/Myanmar seeking to defend Buddhism against mainly the Muslim minority, with monks delivering nationalist anti-Muslim sermons to huge audiences. The aim of this article is to demonstrate how a discriminatory nationalist agenda can - by appealing to the common trope of Buddhism-in-danger - appear to be justified to Buddhists. Based mainly on nationalist sermons, as well as on fieldwork and nationalist publications, this article examines discourse on the Buddha as a nationalist. First, it argues that Burmese Buddhist nationalism, analytically, should be understood as a ressentiment ideological discourse that also informs a Buddhist-nationalist discipline claimed to bring karmic merit. Second, it traces the roots of this ideology to the colonial period. Third, the article outlines and seeks to define how Buddhist nationalism' should be understood in an emic sense.
Keywords: Buddhism; Buddhist nationalism; Burma/Myanmar; Ma Ba Tha; Nationalism; Religion And Politics